Self-expandable nitinol stent placement in homocysteinemic porcine aorta (Clinics, 2008)
PURPOSE: To compare aortic intimal thickening of normal and hyperhomocysteinemic pigs (induced with a methionine-rich diet) following placement of a self-expanding nitinol stent. METHODS: Eighteen Macau pigs were used. They were older than eight weeks in age and had an average weight of 30 kg. Pigs were randomly divided into two groups. The first, Group C (control), was fed a regular diet, and the second group, Group M, was fed a methionine-rich diet for 30 days to induce hyperhomocysteinemia. The self-expandable nitinol stents were 25mm in length and 8 mm in diameter after expansion. Blood samples were collected to measure total cholesterol, triglycerides, HDL and homocysteine concentrations. All animals were subjected to angiography. Thirty days after the procedure, the animals were sacrificed, and the abdominal aorta was removed for histological and digital morphometry analysis. RESULTS: Under microscopic evaluation, the intima was significantly thicker in Group C than in Group M. When groups were compared by digital morphometric analysis, intimal thickening of the vessel wall was higher in Group C than in Group M. There was no significant change in total cholesterol, triglycerides or HDL concentrations in either group. In group C the levels of plasma homocysteine ranged from 14,40 to 16,73µmol/l; in Group M, plasma homocysteine levels ranged from 17.47 to 59.80 µmol/l after 30 days of a methionine-rich diet. CONCLUSION: Compared to normal pigs, less intimal hyperplasia was observed in the abdominal aortas of hyperhomocysteinemic pigs thirty days after the insertion of a self-expandable nitinol stent.